1986
DOI: 10.1002/pen.760260702
|View full text |Cite
|
Sign up to set email alerts
|

Finite element simulation of fountain flow in injection molding

Abstract: Fountain flow is the phenomenon of deceleration and outward motion of fluid particles as they approach a slower moving interface. The use of a general purpose finite element program for the appropriate boundary conditions made possible the detailed flow description behind an advancing liquid front moving at constant speed inside two-dimensional channels and tubes. The results were qualitatively the same for both Newtonian and shear-thinning fluids.he term "fountain effect" was apparently FLOW GEOMETRY AND MATH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
4

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(79 citation statements)
references
References 20 publications
5
70
0
4
Order By: Relevance
“…2. This prediction is qualitatively in agreement with the results of FEM calculations 7) and more elaborate calculations by using conformal mapping. 12,13) In principle, the constant F (or equivalently, the constant r 0 , see eq.…”
Section: Bulk Regionsupporting
confidence: 81%
See 3 more Smart Citations
“…2. This prediction is qualitatively in agreement with the results of FEM calculations 7) and more elaborate calculations by using conformal mapping. 12,13) In principle, the constant F (or equivalently, the constant r 0 , see eq.…”
Section: Bulk Regionsupporting
confidence: 81%
“…Indeed, FEM calculations and experiments suggest that the velocity fields at the flow front are not very sensitive to the constitutive equation. 7,8) Our rather simple theory may therefore capture a universal feature of the fluid dynamics of soft matters at the flow front. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang (1978) attempted a detailed numerical solution using the marker-and-cell method, but his formulation violates symmetry near the interface. Silliman (1979), Lowndes (1980), andMavridis et al (1986a) have used the finite-element method to accurately calculate the flow field, but none of these has focused on the details of the deformation of material as it moves through the flow. Very recently Mavridis et al (1986b) did focus on this problem, but as will be shown later captured only part of the deformation.…”
Section: Introductionmentioning
confidence: 99%